Leader-Follower Well-Being Cross-Over Effect Mediated by Leadership Style - Przemysław ZBIEROWSKI; Milena GOJNY-ZBIEROWSKA (Communications of International Proceedings, 2020)
Well-being of employees is largely dependent on behaviors of leaders. But does it matter for the happiness of followers if the leader is happy as well? And do happy leaders behave differently towards their subordinates than unhappy ones? In this study we make an attempt to unpack the mechanism of cross-over of well-being from the leader to the follower. Specifically, we consider both direct relationship involving emotional contagion and indirect relationship mediated by perceived support and empowerment. Using the responses from 406 leader-follower dyads we find that the well-being cross-over effect is both direct and indirect. Moreover, we find that behavior of the leader are strongly dependent on level of well-being. Happy leaders are more supportive towards their followers and more likely to give away some of the power.
Keywords: Leader’s well-being; follower’s well-being; well-being cross-over effect; social support; empowerment.